Mixed species plantations and their potential role in innovative production systems for forest restoration - López Sampson, A.; Chesnes, M.; Baral, H. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Large-scale timber plantations are controversial in many parts of the world for numerous reasons, including direct and indirect land-use changes and associated impacts on a variety of ecosystem goods and services. The use of mixed-species plantations for commercial and restoration reforestation purposes is gaining interest both as an option to support the supply of wood, and to contribute to meeting international agendas on the restoration and provision of ecosystem services. This review synthesizes the state of mixed-species plantations in South and Southeast Asia, Latin America and sub-Saharan Africa, examining their potential role as a novel production system.